US Public School Operations During the COVID-19 Pandemic: A Scoping Review - Roberto Henry; Megan E. Collins; Katherine A. Connor; Gigi Kwik Gronvall; Tara Kirk Sell (Health Security, 2026)
The COVID-19 pandemic forced the sudden closure of schools and a transition to remote learning across the United States. The suspension of in-person education not only altered the delivery of education for millions of students, but it effectively separated many students from vital services and functions that supported their ability to learn and develop. Given the unique role that schools play in educating children and young adults, as well as providing important nonacademic services, their closures led to disruptions in learning, added familial responsibilities, and reduced access to critical social services for students. The reopening of schools for in-person learning or the continuation of remote learning during a public health emergency requires careful planning and consideration to not only ensure the health and safety of students and staff, but also ensure equitable continuation of education and access to nonacademic services. We conducted a scoping review to identify and characterize the literature related to the implementation and impact of interventions and policies used to operate K-12 public schools in the United States during the first 2 years of the COVID-19 pandemic. Through thematic analysis, we found that masking, ventilation, physical distancing, testing, contact tracing, quarantine and isolation, and vaccination interventions allowed schools to safely conduct in-person learning during the pandemic. Findings from the literature suggest that there are suitable mitigation measures that allowed for the safe operation of public schools during the COVID-19 pandemic. The effective implementation of these measures required adequate resources, leadership commitment, and community buy-in.